TRAINING STAND OR WATER AEROBICS? A COMPARATIVE STUDY OF THE BENEFITS OF TREATING OSTEOPOROSIS IN THE ELDERLY. (Fiep Bulletin - online, 2012)
This study aimed to conduct a comparative analysis of the paths leading to the pursuit of the elderly resistance training (RT) and / or water aerobics as practices that benefit the treatment of osteoporosis, as well as factors that lead to stay in the chosen activity. The study was conducted in the city of Caieiras / SP, in the period from June to August 2011. We selected nine subjects aged between 60 and 80 of these, four were practitioners of Resistance Training and five water aerobics. All subjects exercised the activity for more than a year for medical referral. The instrument used was a questionnaire, composed of fifteen items, contemplated the profile, the degree of disease activity and the environment of the results obtained to date research. The instrument was administered to elderly people who practiced resistance training and / or water aerobics at three sites: two sites of a gym (Qualivida), considered the best city in Resistance Training and Sports Center Municipal Water aerobics is a reference in that region. Data analysis was used Bardin. The results show that osteoporosis is routed to one or other activity by health professionals (in this case, physicians) from the level of disease and the general conditions of the patient, without considering a change of environment-related social problems, trauma or inappropriate use of exercises to meet the same; show also that both act effectively in the treatment of osteoporosis, even with greater adherence to physical activity on water.
Keywords: Osteoporosis; resistance training; aerobics; elderly